1988
DOI: 10.1109/59.192904
|View full text |Cite
|
Sign up to set email alerts
|

The Rockport plant-analysis of temporary fast turbine valving tests

Abstract: A series of temporary fast turbine v a l v i m) field tests were carried out on AEP's Rockport 1300 MW unit. These four tests at various unit loading levels verified the functional aspects of the TFTV scheme-including the control and intercept valve stroke characteristics and the rapid reduction of mechanical driving power. This paper presents an analysis of the mechanical and electrical performance characteristics of the Rockport unit during TFTV. A comparison of the test measurements with digital simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 3 publications
(1 reference statement)
0
7
0
Order By: Relevance
“…The curves in Fig. 3 are typical curves obtained based on information taken from [7][8][9][11][12][13][14] which present different curves for various FV schemes, according to manufacturer information, design characteristics and field tests. All the characteristics presented in the cited references are similar and the curves in Fig.…”
Section: Fast Valvingmentioning
confidence: 99%
See 3 more Smart Citations
“…The curves in Fig. 3 are typical curves obtained based on information taken from [7][8][9][11][12][13][14] which present different curves for various FV schemes, according to manufacturer information, design characteristics and field tests. All the characteristics presented in the cited references are similar and the curves in Fig.…”
Section: Fast Valvingmentioning
confidence: 99%
“…However, it is not recommended because the sudden drop in pressure that occurs when both valves are closing could affect the boiler and control systems negatively [8]. It is also observed that even though the valves could take around up to 6 s to completely open again, P m reacts faster and goes back to the initial value in less time, approximately 2-3 s, as shown in [7,[11][12][13][14] where the P m output versus time curve characteristics are presented, for different turbines in a FV scheme. Initial research on FV considered feasible its application in fossil-fired and nuclear units.…”
Section: Fast Valvingmentioning
confidence: 99%
See 2 more Smart Citations
“…on the AEP System, extensive hfFW testing was performd on the first Rockport unit before this unit came in service in December 1984 [4]. The testing included evaluation of valve strokes, generator electrical quantities and unit thermal characteristics, as a result of fast valving operations with the unit at various load levels.…”
Section: Mftv Equipmentmentioning
confidence: 99%